Religiøst medborgerskap Funksjonshemming, likeverd og menneskesyn - Lid, Inger Marie; Solevåg, Anna Rebecca (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"This anthology examines and elucidates how variation in ability (physical and cognitive) as a human condition impacts participation in religious communities and theology and diakonia as professional disciplines. Functional impairment and disability are meaningful human experiences that are important to explore critically and constructively, in a Norwegian context as well. Fellowship - that everyone is entitled to equal conditions and opportunities for participation in a society - is also relevant in the context of religion, theology and diakonia. Religious fellowship comprises among other things the possibility of being able to choose religious participation and to be religiously active, for example through degrees of association and social participation, employment and volunteer work. Many people have experienced exclusion from participation in religious practices and communities due to specific attitudes or physical barriers. This anthology presents new research on a variety of topics relating to religious fellowship with a focus on equality, human rights and views of humanity. The contributors are from varying fields, including social welfare, public health, social science, literary studies, diakonia, theology and religious studies."